VITAMIN D STATUS IN COVID-19 PATIENTS ADMITTED TO THE CRITICAL CARE UNIT OFAN EASTERN INDIA HOSPITAL - Avijit Saha; Sangeeta Ghosh; Sandip Ghosh; Sanjay Vashistha; Tapas Kumar Sur (Exploratory Animal and Medical Research, 2023)
The COVID-19 patients experienced acute respiratory distress during their SARS-CoV-2 infections. The present observational study was undertaken to find out the possible association between vitamin D and COVID-19 clinical severity in a tertiary care hospital from November 2021 to February 2022. Patients admitted to the hospital’s Critical Care Unit (CCU) with SARS-CoV-2 illness were selected for blood vitamin D estimations. Patients’ conditions were evaluated clinically and correlated with serum vitamin D levels. Out of a total of 97 COVID-19 patients selected, 64.9% were male. Clinically, 41.3% of patients had a severe COVID-19 infection, compared to a moderate infection incidence of 58.7%. Among them, 19.6% and 42.2% were found to be vitamin D deficient and vitamin D insufficient, respectively. Serum vitamin D was significantly (p<0.001) reduced with age (≤ 60 yrs vs. ≥ 60 yrs) and with disease severe (moderate vs. severe). The insufficiency/deficiency of vitamin D was higher among the aged acute respiratory-infected COVID-19 patients. Therefore, vitamin D deficiency may be one of the main causes of severe illness in SARS-CoV-2 patients.